A large-size, low-resistivity 4H silicon carbide crystal rod, a low-resistivity 4H silicon carbide wafer, and a method for preparing them.
By adding solid-phase yttrium nitride during crystal growth, the resistivity distribution of the 4H silicon carbide crystal rod is controlled to make it U-shaped, which solves the problem that it is difficult to obtain a 4H silicon carbide crystal rod with a large thickness and uniform resistivity in the prior art, and achieves a low resistivity and uniform resistivity distribution, which improves the quality and production cost of the wafer.
Patent Information
- Application Number
- CN202411546269.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
It is difficult to obtain a 4H silicon carbide crystal rod with a thickness of more than 15 mm, a resistivity between 12 mΩ·cm and 15 mΩ·cm and a uniform resistivity distribution in the prior art, and polycrystalline silicon carbide is easily broken down at high voltages, limiting its application range.
By placing silicon carbide powder in the crucible and installing crystals, nitrogen and helium are introduced for crystal growth, solid-phase yttrium nitride is added to supplement nitrogen doping, the resistivity distribution of the crystal rod is controlled to make it U-shaped, and the uniformity of axial and radial resistivity distribution is improved.
The low resistivity and uniformity of the resistivity distribution of 4H silicon carbide crystal rod with a thickness of more than 15 mm is achieved, which reduces the stress of the crystal rod, avoids cracking, and improves the production cost and product quality of the wafer.
Smart Images

Figure CN119041030B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a large-size, low-resistance 4H silicon carbide crystal rod, a low-resistance 4H silicon carbide wafer and a preparation method, and belongs to the technical field of preparation of N-type silicon carbide single crystal materials. Background Art
[0002] Compared with traditional silicon-based devices, 4H silicon carbide materials doped with nitrogen have lower losses, higher operating voltages, and better on-resistance, so they are widely used in new electronic power devices. The on-resistance of power devices is affected by several factors, including the resistivity of the substrate, the doping concentration of the epitaxial layer, the contact resistance of the electrode, etc. The difficulty lies in reducing the resistivity of the substrate.
[0003] The resistivity of the substrate accounts for about 30% of the on-resistance of the entire device. The resistivity of 4H silicon carbide substrates on the market is generally between 15 and 25 mΩ·cm. Continuing to reduce the resistance means increasing the nitrogen doping content, which will lead to increased stress. This stress accumulates on the crystal rod as the thickness increases, and it is very likely to cause the crystal rod to crack in the end. It is difficult to obtain crystals with a thickness of more than 15 mm. In addition, the crystal growth process will also cause problems of uneven axial (large difference in resistivity between the silicon and carbon surfaces) and radial (in-plane) resistivity.
[0004] The current way to achieve lower resistivity is to manufacture polycrystalline 4H silicon carbide wafers, etc. However, polycrystalline is more easily broken down under high voltage, which limits the application scope of silicon carbide substrates. Therefore, there is currently a lack of a 4H silicon carbide crystal rod with a thickness of more than 15mm, a resistivity greater than 12mΩ·cm and less than 15mΩ·cm, and a uniform resistivity distribution. Summary of the invention
[0005] In order to solve the above problems, a large-size, low-resistance 4H silicon carbide crystal rod is provided, which has the advantages of a thickness of more than 15 mm, a resistivity at any position greater than 12 mΩ·cm and less than 15 mΩ·cm, and a more uniform resistivity distribution in the axial and radial directions.
[0006] According to one aspect of the present application, a large-size, low-resistance 4H silicon carbide crystal rod is provided, wherein the thickness of the 4H silicon carbide crystal rod is greater than 15 mm, the resistivity of the 4H silicon carbide crystal rod at any position is greater than 12 mΩ·cm and less than 15 mΩ·cm, the resistivity difference within the surface of the 4H silicon carbide crystal rod is less than 0.5 mΩ·cm, and the resistivity difference between the silicon surface and the carbon surface of the 4H silicon carbide crystal rod is less than 1 mΩ·cm.
[0007] Preferably, the resistivity difference within the plane of the 4H silicon carbide crystal rod is below 0.5 mΩ·cm, preferably below 0.43 mΩ·cm.
[0008] Preferably, the resistivity difference between the silicon side and the carbon side of the 4H silicon carbide crystal rod is less than 0.42 mΩ·cm.
[0009] Optionally, the resistivity difference between any two points on any axis of the 4H silicon carbide crystal rod is less than 2 mΩ·cm.
[0010] Preferably, the resistivity difference between any two points on any axis of the 4H silicon carbide crystal rod is less than 1 mΩ·cm.
[0011] The axial resistivity distribution function of the 4H silicon carbide crystal rod is R = ax + bx 2 +cx 3 +d;
[0012] Where R is the resistivity at the test point, in mΩ·cm, x is the vertical distance between the test point and the silicon surface of the 4H silicon carbide crystal rod, in mm, the value range of a is -0.08~0, the value range of b is -0.001~0, the value range of c is 0~0.001, and the value range of d is 13~15.
[0013] If it is a normal N-type 4H silicon carbide crystal rod, its resistivity trend is gradually increasing from the silicon surface to the carbon surface, and the axial distribution uniformity of the overall resistivity of the crystal rod is poor. The resistivity distribution of the 4H silicon carbide crystal rod of the present application is U-shaped, which means that the carbon surface and silicon surface of the crystal rod have high resistivity, and the resistivity at the center is low. This trend is obtained by regulation and control of the present application, which can significantly reduce the difference between the carbon surface and the silicon surface of the crystal rod and improve the axial distribution uniformity of the resistivity of the crystal rod.
[0014] The resistivity of the 4H silicon carbide crystal rod is tested using a variable frequency eddy current device, which can test the resistivity at different depths.
[0015] Optionally, the 4H silicon carbide crystal rod includes a peripheral region, a transition region and a central region from the outside to the inside, the peripheral region is within 10 mm from the outer edge of the 4H silicon carbide crystal rod, and the diameter of the central region is not greater than 20 mm;
[0016] In the 4H silicon carbide wafer obtained by cutting the 4H silicon carbide crystal rod, the ratio of the resistivity of the peripheral area to the resistivity of the central area is 1.02-1.03.
[0017] Optionally, the 4H silicon carbide crystal rod is cut to obtain a 4H silicon carbide wafer, and the in-plane resistivity of any 4H silicon carbide wafer conforms to the formula: U1=R1 / R2, wherein U1 is 1.02~1.03, R1 represents the resistivity of the peripheral area of the 4H silicon carbide wafer, and R2 represents the resistivity of the central area of the 4H silicon carbide wafer.
[0018] Optionally, the 4H silicon carbide crystal rods are on the same horizontal plane, and the resistivity increases from the center to the edge.
[0019] Optionally, the single crystal ratio of the 4H silicon carbide crystal rod is 100%.
[0020] According to another aspect of the present application, a low-resistance 4H silicon carbide wafer is provided, wherein the resistivity of the 4H silicon carbide wafer at any position is greater than 12 mΩ·cm and less than 15 mΩ·cm, the resistivity difference within the surface of the 4H silicon carbide wafer is less than 0.5 mΩ·cm, and the resistivity difference between the upper surface and the lower surface of the 4H silicon carbide wafer is less than 0.1 mΩ·cm.
[0021] Optionally, the 4H silicon carbide wafer includes a peripheral region, a transition region and a central region from the outside to the inside, the peripheral region is within 10 mm from the outer edge of the 4H silicon carbide crystal rod, and the diameter of the central region is not greater than 20 mm;
[0022] In the 4H silicon carbide wafer, the ratio of the resistivity of the peripheral region to the resistivity of the central region is 1.02-1.03.
[0023] Optionally, the in-plane resistivity of the 4H silicon carbide wafer conforms to the formula: U1=R1 / R2, wherein U1 is 1.02~1.03, R1 represents the resistivity of the peripheral area of the 4H silicon carbide wafer, and R2 represents the resistivity of the central area of the 4H silicon carbide wafer.
[0024] Optionally, the single crystal ratio of the 4H silicon carbide wafer is 100%.
[0025] According to another aspect of the present application, a method for characterizing resistivity uniformity of a large-size, low-resistance 4H silicon carbide crystal rod as described in any of the above items is provided, wherein the 4H silicon carbide crystal rod includes a peripheral region, a transition region, and a central region from the outside to the inside, wherein the peripheral region is within 10 mm from the outer edge of the 4H silicon carbide crystal rod, and the diameter of the central region is not greater than 20 mm. The 4H silicon carbide crystal rod is cut to obtain a plurality of 4H silicon carbide wafers, and a head wafer, a tail wafer, and a middle wafer are selected as test objects, wherein the head wafer is the first 4H silicon carbide wafer including the silicon surface of the 4H silicon carbide crystal rod, the middle wafer is the 4H silicon carbide wafer with the lowest resistivity among at least three 4H silicon carbide wafers in the middle region of the 4H silicon carbide crystal rod, and the tail wafer is the last 4H silicon carbide wafer including the carbon surface of the 4H silicon carbide crystal rod;
[0026] The characterization formula of the in-plane uniformity of the 4H silicon carbide crystal rod is:
[0027] U1=R1 / R2, where U1 represents the in-plane uniformity, R1 represents the resistivity of the peripheral area of the head piece, tail piece or middle piece, and R2 represents the resistivity of the central area of the head piece, tail piece or middle piece. If U1 of the head piece, tail piece and middle piece are all in the range of 1.02~1.03, it means that the resistivity of the 4H silicon carbide crystal rod is uniform in the plane.
[0028] This application uses three test objects, namely the head piece, the tail piece and the middle piece, to evaluate the in-plane uniformity and axial uniformity according to the above formula. This is based on the properties of the above-mentioned 4H silicon carbide crystal rod itself. The 4H silicon carbide crystal rod prepared by this process has good overall uniformity, a small in-plane uniformity difference and a trend of being high on both sides and low in the middle in the axial direction. Therefore, three test pieces can be used to evaluate the in-plane uniformity and axial distribution uniformity of the overall 4H silicon carbide crystal rod.
[0029] Optionally, the characterization formula of the axial uniformity of the 4H silicon carbide crystal rod is:
[0030] R3=ax+bx 2 +cx 3 +d;
[0031] Where R3 is the average value of R1 and R2 of the head piece, tail piece or middle piece, and the unit is mΩ·cm. x is the vertical distance between the head piece, tail piece or middle piece and the silicon surface of the 4H silicon carbide crystal rod, and the unit is mm. The value range of a is -0.08~0, the value range of b is -0.001~0, the value range of c is 0~0.001, and the value range of d is 13~15. If the head piece, tail piece and middle piece of the 4H silicon carbide crystal rod all follow this formula, it means that the resistivity of the 4H silicon carbide crystal rod is uniform in the axial direction.
[0032] Optionally, the resistivity R2 of the central area is an average value of the resistivity at test points including at least the midpoint.
[0033] Under this setting, the resistivity R2 of the central area can be only the resistivity value of the midpoint, or it can be the average value of the resistivity of the midpoint and other test points outside the midpoint. In order to further improve the accuracy of the characterization method, the resistivity R2 of the central area is the average value of the resistivity at the midpoint of the central area and at least two test points outside the midpoint.
[0034] Optionally, the resistivity R2 of the central area is an average value of the resistivity at the midpoint of the central area and at least two test points other than the midpoint, and except for the test point at the midpoint of the central area, the other test points are evenly distributed in a circular shape.
[0035] Preferably, the resistivity R2 of the central area is an average value of the resistivity at the midpoint of the central area and at least 12 test points other than the midpoint.
[0036] Optionally, the distance between the remaining test points outside the center in the central area and the center is 15 mm.
[0037] The distance here can improve the accuracy of the characterization method. If the distance between the remaining test points and the midpoint is farther, the difference in resistivity will be greater, which will reduce the accuracy of the characterization method to a certain extent.
[0038] Optionally, the resistivity R1 of the peripheral area is an average value of the resistivity at at least two evenly distributed test points in the peripheral area;
[0039] The distance between the test point in the peripheral area and the transition area is 3-5 mm.
[0040] The distance here can improve the accuracy of the characterization method. If the distance from the transition area is greater, the test point is more biased towards the edge of the crystal rod. Some uneven edges will introduce test errors and reduce the accuracy of the characterization method.
[0041] Preferably, the resistivity R1 of the peripheral area is an average value of the resistivity at at least 7 evenly distributed test points in the peripheral area.
[0042] The more test points there are in the peripheral area, the more representative the value of the resistivity R2 of the central area is. However, the more test points there are, the longer the test time will be, thus reducing the characterization efficiency of the characterization method.
[0043] According to another aspect of the present application, a method for preparing a large-size, low-resistance 4H silicon carbide crystal rod is provided, comprising the following steps:
[0044] (1) placing the raw materials in a crucible, installing a seed crystal in the crucible, removing impurities, and heating to 2100-2300K for crystal growth. During this period, nitrogen and helium are introduced. The amount of nitrogen introduced is 80-120 g / L, and the amount of helium introduced is 40-60 g / L. The crystal growth lasts for a short time.
[0045] (2) Then the temperature is raised to 2400-2500K and the crystal growth is continued until the second time, during which solid-phase yttrium nitride is added for supplementary nitrogen doping;
[0046] (3) Finally, the temperature is raised to 2550-2650K to end the crystal growth. During the heating period, the amount of helium introduced is reduced to 1-2g / L. After cooling, 4H silicon carbide crystal rods are obtained.
[0047] The helium atoms introduced in step (1) of the method are relatively light and are more evenly distributed than nitrogen at high temperatures. Firstly, the nitrogen distribution can be more evenly distributed. Secondly, the temperature difference within the surface of the seed crystal and the newly formed crystal on the seed crystal can be less than 1.5K. The above two effects can significantly improve the in-plane uniformity of the resistivity of the 4H silicon carbide crystal rod, so that the resistivity difference within the surface of the 4H silicon carbide crystal rod is less than 0.5 mΩ·cm.
[0048] Under normal circumstances, due to the radial temperature difference between the edge and the center, the step height is inconsistent, and it can even be said that the difference is tens to hundreds of microns. In step (2), due to the increase in temperature, the content of doped nitrogen will decrease significantly. At this time, the solid phase yttrium nitride is used to supplement the nitrogen doping of silicon carbide. Yttrium nitride decomposes at high temperature, which not only provides nitrogen elements, but also has a large covalent radius of yttrium elements and is basically unable to be doped into silicon carbide. In this way, yttrium elements can flow in the growth space along with the flow field. Yttrium elements will make the growth step heights of the edge and the center approximately the same, which will make the resistivity of the edge and the center more uniform. Therefore, yttrium elements will not be doped into the silicon carbide lattice, but it will change the morphology of the crystal, increase the nitrogen doping content of the crystal, and thus reduce the resistivity. In addition, solid phase yttrium nitride is evenly distributed in the raw material, which can continue to maintain the uniformity of doping, thereby continuing to maintain the uniformity of in-plane resistivity. Since the temperature rises and the doping content decreases in the later stage of crystal growth, the above-mentioned preparation method controls the stability of the step height by the flow of yttrium element on the growth interface, thereby obtaining the silicon carbide crystal and substrate of the present application. Those skilled in the art can also obtain the silicon carbide crystal of the present application by other preparation methods to make the step size of the crystal more stable. Therefore, the above-mentioned preparation method does not constitute a limitation on the structure and performance of the silicon carbide crystal in the present application.
[0049] In step (3), the temperature is further increased, and the doping method is still to provide doping simultaneously with solid-phase yttrium nitride and nitrogen. The axial resistivity will increase. Therefore, under the preparation of steps (1) to (3), the resistivity of the 4H silicon carbide crystal rod in the axial direction can be U-shaped, reducing the difference in resistivity between the carbon surface and the silicon surface, and improving the resistivity distribution uniformity of the 4H silicon carbide crystal rod.
[0050] Those skilled in the art will appreciate that the raw material in step (1) refers to a raw material that can be heated and sublimated to grow silicon carbide crystals, including but not limited to silicon carbide powder, carbon powder and silicon powder.
[0051] Optionally, in step (1), the ratio of nitrogen to helium is 2:1.
[0052] The introduction ratio of nitrogen to helium is 2:1, which can further improve the uniformity of nitrogen doping and the temperature uniformity during the crystal growth process, thereby achieving the best growth quality of the crystal.
[0053] Optionally, the first time is 15-30 hours, and the second time is 15-30 hours.
[0054] Optionally, the weight ratio of the solid phase yttrium nitride in step (2) to the raw material in step (1) is 1:(100-150).
[0055] Adding too much or too little solid-phase yttrium nitride will cause a drastic change in the carbon-silicon ratio in the atmosphere of raw material sublimation, affecting the stability of crystal growth, and may cause nucleation problems, thereby affecting the thickness of the crystal.
[0056] Optionally, the amount of helium introduced during the heating period in step (3) is reduced to 1-2 g / L. In the early stage of growth, the in-plane uniformity of the resistivity of the crystal is already high and lays the foundation for the uniformity of the resistivity in the later stage. The heating rate in the later stage is relatively slow, and the reduction of helium will basically not change the distribution uniformity of the in-plane resistivity, and can significantly reduce costs.
[0057] Optionally, during the process of heating to 2400-2500K in step (2), the heating rate is 15-20K / h. This moderate heating rate can make the silicon carbide atmosphere grow evenly on the seed crystal, improve the resistivity uniformity, reduce the stress inside the crystal, and reduce the generation of defects.
[0058] Optionally, the heating rate of step (3) to 2550-2650K is 3-4K / h, and the heating rate in the later stage is relatively gentle, which improves the atmosphere stability in the crucible, basically does not change the distribution uniformity of the in-plane resistivity, and can also reduce stress and defects, thereby improving the crystallization quality of the crystal.
[0059] According to another aspect of the present application, provided is an application of a 4H silicon carbide crystal rod prepared by a preparation method of the large-size, low-resistance 4H silicon carbide crystal rod described in any of the above items, or the low-resistance 4H silicon carbide wafer described in any of the above items, or the large-size, low-resistance 4H silicon carbide crystal rod described in any of the above items in a semiconductor device.
[0060] The beneficial effects of this application include but are not limited to:
[0061] 1. The large-size, low-resistance 4H silicon carbide crystal rod of the present application has a thickness of more than 15 mm and a resistivity difference between the upper and lower surfaces (carbon side and silicon side) of the crystal rod of less than 1 mΩ·cm, which proves that the axial resistivity distribution of the crystal rod is more uniform. Therefore, the crystal rod can be cut to obtain a larger number of 4H silicon carbide wafers, thereby reducing the production cost of 4H silicon carbide wafers and improving the production quality of 4H silicon carbide wafers.
[0062] 2. The large-size, low-resistance 4H silicon carbide crystal ingot of the present application can reduce the stress of the entire crystal ingot, improve the quality of the crystal ingot and avoid cracking of the crystal ingot on the basis of reducing the resistivity and achieving uniform distribution of the resistivity in the axial and radial directions.
[0063] 3. According to the large-size, low-resistance 4H silicon carbide crystal rod of the present application, the resistivity distribution is U-shaped, so the resistivity difference between the upper and lower surfaces of the crystal rod is small, and the resistivity difference between the upper and lower surfaces of the wafer obtained by cutting the crystal rod is even smaller, and the performance of the device prepared by the wafer is better and the stability is better.
[0064] 4. The method for characterizing the resistivity uniformity of large-size, low-resistance 4H silicon carbide crystal rods of the present application uses three representative 4H silicon carbide wafers, namely the head wafer, the tail wafer and the middle wafer, as test objects, which can intuitively reflect the distribution uniformity of the crystal rod in the axial and radial directions, thereby providing a basis for the application of silicon carbide substrates, with short test time, good accuracy of test results and high reliability.
[0065] 5. The method for characterizing the resistivity uniformity of the large-size, low-resistance 4H silicon carbide crystal rod of the present application, the characterization formula of the in-plane uniformity is expressed by the ratio of the resistivity R1 of the peripheral area to the resistivity R2 of the central area, and the closer the ratio is to 1, the better the in-plane uniformity of the 4H silicon carbide crystal rod; the axial resistivity of the 4H silicon carbide crystal rod is predicted by a three-term formula, and the axial uniformity of the crystal rod is characterized by comparing the resistivity of the head piece, the tail piece and the middle piece with the predicted value of the formula, which can significantly improve the characterization efficiency of the 4H silicon carbide crystal rod.
[0066] 6. The large-size, low-resistance 4H silicon carbide crystal rod and wafer of the present application can reduce basal plane dislocations and stacking faults while reducing resistivity, further improving the performance of silicon carbide materials and broadening the application range of silicon carbide materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0068] Figure 1 Schematic diagram of the axial resistivity distribution of the 4H silicon carbide crystal rod prepared in Example 3 of the present application.
[0069] Figure 2 A time-temperature curve of a 4H silicon carbide crystal rod prepared in Example 3 of the present application;
[0070] Figure 3 This is a distribution diagram of the resistivity R2 test points in the central area and the resistivity R1 test points in the peripheral area involved in Example 7 of the present application. DETAILED DESCRIPTION
[0071] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0072] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.
[0073] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.
[0074] Example 1
[0075] This embodiment relates to a method for preparing a large-size, low-resistance 4H silicon carbide crystal rod, comprising the following steps:
[0076] (1) Place silicon carbide powder in a crucible, install a seed crystal in the crucible, remove impurities, and heat to 2100K for crystal growth. During this period, nitrogen and helium are introduced. The nitrogen introduction rate is 80g / L and the helium introduction rate is 40g / L. The crystal growth lasts for 30 hours.
[0077] (2) then heating the mixture to 2400 K at a heating rate of 15 K / h and continuing the crystal growth for 30 hours, during which solid-phase yttrium nitride was added for supplementary nitrogen doping, wherein the weight ratio of the added solid-phase yttrium nitride to the silicon carbide powder in step (1) was 1:100;
[0078] (3) Finally, the temperature was raised to 2550 K at a heating rate of 4 K / h to terminate the crystal growth. During the heating period, the amount of helium introduced was reduced to 1 g / L. After cooling, 4H silicon carbide crystal rods were obtained.
[0079] Example 2
[0080] This embodiment relates to a method for preparing a large-size, low-resistance 4H silicon carbide crystal rod, comprising the following steps:
[0081] (1) Place silicon carbide powder in a crucible, install a seed crystal in the crucible, remove impurities, and heat to 2300K for crystal growth. During this period, nitrogen and helium are introduced. The nitrogen introduction rate is 120g / L and the helium introduction rate is 60g / L. The crystal growth lasts for 15h.
[0082] (2) then heating the mixture to 2500 K at a heating rate of 20 K / h and continuing the crystal growth for 15 h, during which solid-phase yttrium nitride was added for supplementary nitrogen doping, wherein the weight ratio of the added solid-phase yttrium nitride to the silicon carbide powder in step (1) was 1:150;
[0083] (3) Finally, the temperature was raised to 2650 K at a heating rate of 3 K / h to terminate the crystal growth. During the heating period, the amount of helium introduced was reduced to 2 g / L. After cooling, 4H silicon carbide crystal rods were obtained.
[0084] Example 3
[0085] This embodiment relates to a method for preparing a large-size, low-resistance 4H silicon carbide crystal rod, comprising the following steps:
[0086] (1) Place silicon carbide powder in a crucible, install a seed crystal in the crucible, remove impurities, and heat to 2273K for crystal growth. During this period, nitrogen and helium are introduced. The nitrogen introduction rate is 100 g / L and the helium introduction rate is 50 g / L. The crystal growth lasts for 30 hours.
[0087] (2) then heating the temperature to 2473 K at a heating rate of 20 K / h and continuing crystal growth for 20 h, during which solid-phase yttrium nitride is added for supplementary nitrogen doping, and the weight ratio of the added amount of solid-phase yttrium nitride to the silicon carbide powder in step (1) is 1:120;
[0088] (3) Finally, the temperature was raised to 2573 K at a heating rate of 3.3 K / h to terminate the crystal growth. During the heating period, the amount of helium introduced was reduced to 2 g / L. After cooling, 4H silicon carbide crystal rods were obtained.
[0089] The time-temperature curve of preparing 4H silicon carbide crystal rods in this example is shown in Figure 2 .
[0090] Example 4
[0091] The difference between this embodiment and embodiment 3 is that the heating rate in step (2) is 25K / h, and the rest is the same as embodiment 3.
[0092] Example 5
[0093] The difference between this embodiment and embodiment 3 is that the heating rate in step (3) is 5K / h, and the rest is the same as embodiment 3.
[0094] Example 6
[0095] The difference between this embodiment and embodiment 3 is that the weight ratio of the amount of solid-phase yttrium nitride added in step (2) to the amount of silicon carbide powder added in step (1) is 1:80, and the rest is the same as embodiment 3.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 3 is that in step (2), the amount of nitrogen introduced is increased to 150 g / L, but solid phase yttrium nitride is no longer added, and the rest is the same as Example 3.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 3 is that solid-phase yttrium nitride is added in step (1), and the weight ratio of the added amount of solid-phase yttrium nitride to the silicon carbide powder is 1:120. In step (2), solid-phase yttrium nitride is no longer added. The rest is the same as Example 3.
[0100] Test Example 1
[0101] The thickness of the entire crystal rod of the 4H silicon carbide crystal rod prepared in the above embodiments and comparative examples was tested, and the test results are shown in Table 1. The 4H silicon carbide crystal rod prepared in the above embodiments and comparative examples was cut and processed to obtain multiple 4H silicon carbide wafers, each of which had a thickness of 500 μm, wherein the 4H silicon carbide wafer containing the silicon surface of the 4H silicon carbide crystal rod was the head wafer, the 4H silicon carbide wafer containing the carbon surface of the 4H silicon carbide crystal rod was the tail wafer, and the middle wafer was the 4H silicon carbide wafer with the lowest resistivity obtained by cutting the 4H silicon carbide crystal rod. The resistivity distribution and curvature radius distribution of the 4H silicon carbide wafer were tested, and the test results of the resistivity distribution are shown in Table 1.
[0102] 1. Resistivity distribution test method: Each 4H silicon carbide wafer includes a peripheral area, a transition area and a central area from the outside to the inside. The peripheral area is within 10 mm from the outer edge of the 4H silicon carbide wafer, and the diameter of the central area is not more than 20 mm. At least 7 test points are detected in the peripheral area, the transition area and the central area. The average resistivity of all the test points is calculated as the resistivity of the 4H silicon carbide wafer.
[0103] (1) Minimum resistivity: refers to the minimum resistivity value tested among multiple 4H silicon carbide wafers obtained by cutting the entire 4H silicon carbide crystal rod, representing the minimum resistivity value of the entire 4H silicon carbide crystal rod.
[0104] (2) Maximum resistivity: refers to the maximum resistivity value tested among multiple 4H silicon carbide wafers obtained by cutting the entire 4H silicon carbide crystal rod, representing the maximum resistivity value of the entire 4H silicon carbide crystal rod.
[0105] (3) Maximum difference in in-plane resistivity: The difference between the maximum and minimum resistivity values of all test points of each 4H silicon carbide wafer is the in-plane resistivity difference of the 4H silicon carbide wafer. The maximum difference in in-plane resistivity in Table 1 refers to the maximum value of the in-plane resistivity difference among all 4H silicon carbide wafers.
[0106] (4) R1 is used to represent the resistivity of the peripheral area of the head piece, tail piece or middle piece. The resistivity R1 of the peripheral area is the average resistivity of at least two evenly distributed test points in the peripheral area. The distance between the test points in the peripheral area and the transition area is 3-5mm; R2 represents the resistivity of the central area of the head piece, tail piece or middle piece. The resistivity R2 of the central area is the average resistivity of the midpoint of the central area and at least two test points other than the midpoint. The distance between the remaining test points other than the center in the central area and the center is 15mm; U1=R1 / R2, U1 represents the in-plane uniformity, and it is judged whether the U1 of the 4H silicon carbide crystal rod is within the range of 1.02~1.03;
[0107] (5) The resistivity difference between the head piece and the tail piece: represents the resistivity difference between the carbon side and the silicon side of the 4H silicon carbide ingot;
[0108] (6) The maximum axial resistivity difference refers to the difference between the maximum resistivity and the minimum resistivity tested in multiple 4H silicon carbide wafers obtained by cutting the 4H silicon carbide crystal rod, which represents the maximum resistivity difference of the entire 4H silicon carbide crystal rod in the axial direction. The smaller the resistivity difference between the head piece and the tail piece and the maximum resistivity difference, the more uniform the resistivity distribution of the 4H silicon carbide crystal rod in the axial direction.
[0109] (7) According to the resistivity of each 4H silicon carbide wafer, the resistivity distribution function of the entire crystal rod is obtained, and it is determined whether it conforms to the resistivity distribution function R = ax + bx 2 +cx 3 +d; where R is the resistivity at the test point, in mΩ·cm, x is the vertical distance between the test point and the silicon surface of the 4H silicon carbide crystal rod, in mm, a ranges from -0.08 to 0, b ranges from -0.001 to 0, c ranges from 0 to 0.001, and d ranges from 13 to 15. The fitting results are as follows: 2 Value, r 2 The closer it is to 1, the closer it fits the 4H silicon carbide crystal rod to the resistivity distribution function, and when it is greater than 0.98, we consider it a perfect fit.
[0110] Table 1. Resistivity of 4H silicon carbide ingot
[0111]
[0112] The resistivity difference between the head piece and the tail piece in Table 1 is the resistivity difference between the silicon surface and the carbon surface of the 4H silicon carbide crystal rod. The 4H silicon carbide wafers obtained after cutting the 4H silicon carbide crystal rods of the above Examples 1-6 have a resistivity difference between the upper and lower surfaces of less than 0.1 mΩ·cm. The 4H silicon carbide wafers obtained after cutting the 4H silicon carbide crystal rods of Comparative Examples 1 and 2 have a resistivity difference between the upper and lower surfaces of more than 0.1 mΩ·cm.
[0113] According to the data in Table 1, different yttrium nitride contents, heating rates, and yttrium nitride release steps will significantly affect the stress distribution of the 4H silicon carbide crystal rod. Among them, the 4H silicon carbide crystal rod prepared in Example 3 has the lowest stress and the most uniform stress distribution in both the axial and radial directions.
[0114] Figure 1 The resistivity distribution diagram of the 4H silicon carbide crystal rod prepared in Example 3 shows that the resistivity of the 4H silicon carbide crystal rod first decreases and then increases from the silicon surface to the carbon surface, showing a U-shaped distribution. The resistivity difference between the carbon surface and the silicon surface is very small, and the resistivity difference on the overall axis is less than 0.5 mΩ·cm, which proves that the axial distribution uniformity of the resistivity of the 4H silicon carbide crystal rod is good.
[0115] Example 7
[0116] This embodiment relates to a method for characterizing resistivity uniformity of the 4H silicon carbide crystal rod prepared in Examples 1-6. The 4H silicon carbide crystal rod includes a peripheral region, a transition region, and a central region from the outside to the inside. The peripheral region is 6 mm away from the outer edge of the 4H silicon carbide crystal rod, and the diameter of the central region is 20 mm. The 4H silicon carbide crystal rod is cut to obtain a plurality of cut pieces. The head piece, the tail piece, and the middle piece are selected as test objects. The middle piece is the cut piece with the lowest resistivity among the three cut pieces in the middle region of the 4H silicon carbide crystal rod.
[0117] The characterization formula for the in-plane uniformity of 4H silicon carbide ingot is:
[0118] U1=R1 / R2, where U1 represents the in-plane uniformity, R1 represents the resistivity of the peripheral area of the head piece, tail piece or middle piece, and R2 represents the resistivity of the central area of the head piece, tail piece or middle piece. If U1 of the head piece, tail piece and middle piece are all within the range of 1.02-1.03, it means that the resistivity of the 4H silicon carbide crystal rod is uniform in the plane.
[0119] The characterization formula of the axial uniformity of 4H silicon carbide crystal rod is:
[0120] R3=ax+bx 2 +cx 3 +d;
[0121] Where R3 is the average value of R1 and R2 of the head piece, tail piece or middle piece, and the unit is mΩ·cm. x is the vertical distance between the head piece, tail piece or middle piece and the silicon surface of the 4H silicon carbide crystal rod, and the unit is mm. The value range of a is -0.08~0, the value range of b is -0.001~0, the value range of c is 0~0.001, and the value range of d is 13~15. If the head piece, tail piece and middle piece of the 4H silicon carbide crystal rod all follow this formula, it means that the resistivity of the 4H silicon carbide crystal rod is uniform in the axial direction.
[0122] As an implementation method, the resistivity of the central area is the resistivity of the midpoint test point of the head piece, the tail piece or the middle piece, and the resistivity of the peripheral area is the average resistivity of the two evenly distributed test points in the peripheral area. The distance between the test point in the peripheral area and the transition area is 3mm. The distribution of the resistivity test points of the central area and the peripheral area is shown in Figure 3 , where the blue points are the test points.
[0123] As an implementation mode, the resistivity of the central area is the average value of the resistivity at the midpoint of the head piece, the tail piece or the middle piece and the test points other than the two midpoints, wherein the test points other than the two midpoints are evenly distributed in a circle around the midpoint and are 15 mm away from the midpoint; the resistivity of the peripheral area is the average value of the resistivity at 7 evenly distributed test points in the peripheral area, and the distance between the test points in the peripheral area and the transition area is 5 mm.
[0124] As an implementation mode, the resistivity of the central area is the average resistivity at the midpoint of the head piece, the tail piece or the middle piece and the 12 test points other than the midpoint, wherein the test points other than the 12 midpoints are evenly distributed in a circle around the midpoint and are 15 mm away from the midpoint; the resistivity of the peripheral area is the average resistivity at 7 evenly distributed test points in the peripheral area, and the distance between the test points in the peripheral area and the transition area is 3 mm.
[0125] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A large-size, low-resistance 4H silicon carbide crystal rod, characterized in that: The thickness of the 4H silicon carbide crystal rod is greater than 15 mm, the resistivity of the 4H silicon carbide crystal rod at any position is greater than 12 mΩ·cm and less than 15 mΩ·cm, the resistivity difference within the surface of the 4H silicon carbide crystal rod is less than 0.5 mΩ·cm, and the resistivity difference between the silicon surface and the carbon surface of the 4H silicon carbide crystal rod is less than 1 mΩ·cm; The axial resistivity distribution function of the 4H silicon carbide crystal rod is R = ax + bx 2 +cx 3 +d; Where R is the resistivity at the test point, in mΩ·cm, x is the vertical distance between the test point and the silicon surface of the 4H silicon carbide crystal rod, in mm, the value range of a is -0.08~0, the value range of b is -0.001~0, the value range of c is 0~0.001, and the value range of d is 13~15.
2. The large-size, low-resistance 4H silicon carbide crystal rod according to claim 1, characterized in that: The 4H silicon carbide crystal rod includes a peripheral region, a transition region and a central region from the outside to the inside, the peripheral region is within 10 mm from the outer edge of the 4H silicon carbide crystal rod, and the diameter of the central region is not greater than 20 mm; In the 4H silicon carbide wafer obtained by cutting the 4H silicon carbide crystal rod, the ratio of the resistivity of the peripheral area to the resistivity of the central area is 1.02-1.
03.
3. The method for characterizing resistivity uniformity of a large-size, low-resistance 4H silicon carbide crystal rod according to any one of claims 1 to 2, characterized in that: The 4H silicon carbide crystal rod includes a peripheral area, a transition area and a central area from the outside to the inside, the peripheral area is within 10 mm from the outer edge of the 4H silicon carbide crystal rod, and the diameter of the central area is not more than 20 mm. The 4H silicon carbide crystal rod is cut to obtain a plurality of 4H silicon carbide wafers, and a head wafer, a tail wafer and a middle wafer are selected as test objects. The head wafer is the first 4H silicon carbide wafer including the silicon surface of the 4H silicon carbide crystal rod, the middle wafer is the 4H silicon carbide wafer with the lowest resistivity among at least three 4H silicon carbide wafers in the middle area of the 4H silicon carbide crystal rod, and the tail wafer is the last 4H silicon carbide wafer including the carbon surface of the 4H silicon carbide crystal rod; The characterization formula of the in-plane uniformity of the 4H silicon carbide crystal rod is: U1=R1 / R2, where U1 represents the in-plane uniformity, R1 represents the resistivity of the peripheral area of the head piece, tail piece or middle piece, and R2 represents the resistivity of the central area of the head piece, tail piece or middle piece. If U1 of the head piece, tail piece and middle piece are all in the range of 1.02~1.03, it means that the resistivity of the 4H silicon carbide crystal rod is uniform in the plane.
4. The method according to claim 3, characterized in that The characterization formula of the axial uniformity of the 4H silicon carbide crystal rod is: R3=ax+bx 2 +cx 3 +d; Where R3 is the average value of R1 and R2 of the head piece, tail piece or middle piece, and the unit is mΩ·cm. x is the vertical distance between the head piece, tail piece or middle piece and the silicon surface of the 4H silicon carbide crystal rod, and the unit is mm. The value range of a is -0.08~0, the value range of b is -0.001~0, the value range of c is 0~0.001, and the value range of d is 13~15. If the head piece, tail piece and middle piece of the 4H silicon carbide crystal rod all follow this formula, it means that the resistivity of the 4H silicon carbide crystal rod is uniform in the axial direction.
5. A low-resistance 4H silicon carbide wafer, characterized in that: The resistivity of the 4H silicon carbide wafer at any position is greater than 12 mΩ·cm and less than 15 mΩ·cm, the resistivity difference within the surface of the 4H silicon carbide wafer is less than 0.5 mΩ·cm, and the resistivity difference between the upper surface and the lower surface of the 4H silicon carbide wafer is less than 0.1 mΩ·cm; The 4H silicon carbide wafer includes a peripheral region, a transition region and a central region from the outside to the inside, the peripheral region is within 10 mm from the outer edge of the 4H silicon carbide wafer, and the diameter of the central region is not greater than 20 mm; In the 4H silicon carbide wafer, the ratio of the resistivity of the peripheral region to the resistivity of the central region is 1.02-1.
03.
6. A method for preparing a large-size, low-resistance 4H silicon carbide crystal rod, characterized in that: The steps include: (1) placing the raw materials in a crucible, installing a seed crystal in the crucible, removing impurities, and heating to 2100-2300K for crystal growth. During this period, nitrogen and helium are introduced. The amount of nitrogen introduced is 80-120 g / L, and the amount of helium introduced is 40-60 g / L. The crystal growth lasts for a short time. (2) Then the temperature is raised to 2400-2500K and the crystal growth is continued until the second time, during which solid-phase yttrium nitride is added for supplementary nitrogen doping; (3) Finally, the temperature is raised to 2550-2650K to end the crystal growth. During the heating period, the amount of helium introduced is reduced to 1-2g / L. After cooling, 4H silicon carbide crystal rods are obtained.
7. The preparation method according to claim 6, characterized in that: The first time is 15-30 hours, and the second time is 15-30 hours.
8. The preparation method according to claim 7, characterized in that: The weight ratio of the solid phase yttrium nitride in step (2) to the raw material in step (1) is 1:(100-150).
Citation Information
Patent Citations
Device for growing silicon carbide crystals by liquid phase method and crystal growth furnace
CN116516483A
SiC substrate and SiC ingot
CN117166052A
Method of manufacturing silicon carbide single crystal ingot
JP2018168052A
Silicon carbide substrate
US20240254656A1